Motivational interviewing as a tool for nursing care in sexual health: systematic review - Cervantes-Lara, Claudia Alejandra (Universidad de Sonora, 2022)
Introduction: Sexual health is a fundamental aspect for the integral well-being of the person, however, its absence can cause emotional, physical and evidently sexual alterations, these alterations are manifested through public health problems of each region, so the nursing staff has the professional duty to design and test interventions that can solve the needs of the population on aspects of sexuality. Objective: To investigate how motivational interviewing is applied in nursing care for sexual health care in young adult women. Methodology: Systematic review under preferred reporting elements for systematic reviews and meta-analysis in various databases. Articles published from 2017 to 2020 were analyzed, in English, Spanish and Portuguese; using motivational interviewing, sexual health, nursing and women as descriptors. The inclusion criteria used were: application of motivational interviewing as an intervention by nursing on sexual health issues in young adult women. A sample of two articles was obtained. Results: The studies applied motivational interviewing in conjunction with an educational strategy to improve adherence to cervical cytology; knowledge was increased, obtaining favorable results, but these results are not sufficient to make assertions. Conclusion: Motivational interviewing is an intervention whose application in the sexual health of young adult women is limited, making it an opportunity for the development of nursing research.